Endothelin release is augmented with captopril in rat ischemia-reperfusion injury of the liver - (:unkn) unknown (SPRINGER VERLAG, 1996)
The reactive oxygen metabolites (ROMs) and the vascular endothelial factors such as endothelins (ETs) and thromboxane A(2) (TxA(2)) were found to be mediators of the reperfusion component of ischemia-reperfusion (I/R) injury. Captopril (CPT), a sulfydryl (-SH) group containing angiotensin-converting enzyme inhibitor, has been shown to reverse I/R injury by its ROM scavenging effect. In this experimental study, the effects of CPT and BM 13.177 (a TxA(2) receptor antagonist) were assesed on liver I/R injury in rats. Four groups of Wistar albino rats were either sham-operated, control, CPT or BM 13.177-treated. The middle and left lateral hepatic arteries and portal veins were occluded in each group but the sham and the corresponding agents were given to the animals prior to I/R injury. After I/R injury, blood was drawn from the suprahepatic inferior vena cava for ET-l-like activity assay and liver tissue samples were obtained for the determination of prostaglandin E(2) (PCE(2)), leukotriene C-4 (LTC(4)) and histopathologic examination, PGE(2) and ET-1 levels were increased significantly in the control group compared with the sham-operated group. In the CPT group, LTC(4), PGE(2) and ET-I levels were significantly increased compared with the control group, while only ET-I levels were not different from those of the control group in the BM 13.177-treated group. It is concluded that ET-1 release increases in response to I/R injury in rat liver and CPT further increases this release. It also appears that CPT has a stimulatory effect on arachidonic acid metabolism in addition to its free radical scavenging effect.
Keywords: liver; ischemia-reperfusion injury; endothelin; REACTIVE OXYGEN; GUINEA-PIG; MECHANISMS; ILOPROST; ADHESION; CELLS